2016
DOI: 10.1002/etc.3455
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and detoxification responses of oysters Crassostrea hongkongensis in a multimetal‐contaminated estuary

Abstract: The contaminated oysters discovered in the Pearl River Estuary (Guangdong province, China) contained high levels of metals in their tissues, especially Cu and Zn, indicating that this large and densely urbanized estuary in Southern China suffers from serious metal pollution. The present study aimed to investigate the impacts of multimetal pollution in the Pearl River Estuary on oyster antioxidant and detoxification systems. The responses of various biochemical biomarkers in the ecologically important oyster Cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…Nevertheless, in another study the GST activity did not change when mussels M. galloprovincialis were exposed to a similar range of Cu concentrations for 7 days (Maria and Bebianno, 2011) although the inductive effect of Cu could be observed at the level of GST protein expression (Maria et al, 2013). Noteworthy, increased GST activity was also reported for bivalves from metal-polluted marine environments (Fernández et al, 2010;Liu and Wang, 2016;Vidal-Liñán et al, 2014a).…”
Section: Discussionmentioning
confidence: 91%
“…Nevertheless, in another study the GST activity did not change when mussels M. galloprovincialis were exposed to a similar range of Cu concentrations for 7 days (Maria and Bebianno, 2011) although the inductive effect of Cu could be observed at the level of GST protein expression (Maria et al, 2013). Noteworthy, increased GST activity was also reported for bivalves from metal-polluted marine environments (Fernández et al, 2010;Liu and Wang, 2016;Vidal-Liñán et al, 2014a).…”
Section: Discussionmentioning
confidence: 91%
“…The discrepancy between the high expression of NT, as an indicator of the oxidant peroxynitrite generation, and the low detection of MDA, as an indicator of the lipid peroxidation, may rely on the protective effect of the antioxidant systems that prevents cell oxidative damage (Canesi, 2015; Ferreira et al, 2019; Liu & Wang, 2016). In this sense, the limited efficiency of the antioxidant defences and the increased level of lipid peroxidation may have been associated with oyster mortality events (Gènard et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The discrepancy between the high expression of NT, as an indicator of the oxidant peroxynitrite generation, and the low detection of MDA, as an indicator of the lipid peroxidation, may rely on the protective effect of the antioxidant systems that prevents cell oxidative damage (Canesi, 2015;Ferreira et al, 2019;Liu & Wang, 2016).…”
Section: Ta B L E 1 Monthly Prevalence Ofmentioning
confidence: 99%
“…Exposure to water‐borne copper negatively affects bivalve gills’ antioxidant/detoxifying response. For example, Regoli & Principato (1995) have shown inhibition of GST activity in Mytilus galloprovincialis exposed in the laboratory to Cu 2+ , whereas the gills of the oyster Crassostrea hongkongensis accumulated Cu 2+ and showed increased GST activity and lipid peroxidation (Liu & Wang, 2016). In the freshwater bivalve Unio tumidus , Doyotte et al (1997) have observed that exposure to water‐borne Cu 2+ diminished gill antioxidant defenses, except for CAT, and increased lipid peroxidation.…”
Section: Discussionmentioning
confidence: 99%